From Earth to exoplanets: Quantifying atmospheric biosignatures and biogeochemical controls on habitability - Krissansen-Totton, Joshua (My University, 2019)
It will soon be possible to determine the atmospheric composition of potentially habitable planets around other stars via astronomical observations. This raises the exciting possibility of detecting life remotely from its waste gases. But knowing what gases to look for and ruling out non-biological processes may be difficult. Fortunately, Earth is an invaluable natural laboratory for understanding biosignatures and habitability more broadly, as illustrated by this thesis. The first three chapters of this thesis explore chemical disequilibrium as a possible exoplanet biosignature. A rigorous calculation of the disequilibrium in Earth’s atmosphere-ocean system is presented. Earth’s disequilibrium is larger than that of any other Solar System body, and is dominated by the coexistence of N2, O2, and liquid water. This combination is a more compelling biosignature than O2 alone because it would not persist without continuous replenishment of O2. Next, disequilibrium calculations were applied to the early, anoxic Earth (4.0-2.5 Ga). It is found that CH4 and CO2 were out of equilibrium in the Archean. This disequilibrium combination is biogenic because it would not persist without continuous replenishment of CH4 from life. Moreover, this CH4+CO2 biosignature is potentially ubiquitous and detectable with the upcoming James Webb Space Telescope. An assessment of planetary habitability is important contextual information for interpreting any purported biosignature detection. The next two chapters of this thesis investigate how the carbon cycle has maintained habitable conditions on Earth. It is widely believed that the continental weathering thermostat buffered Earth’s climate against a secular solar luminosity increase over Earth history. But exactly how this feedback works, and the role of seafloor weathering—a complimentary climate buffer—is unknown. An inverse carbon cycle model is applied to the last 100 Ma and by fitting proxy data for pCO2, ocean chemistry, and temperature, Earth’s climate sensitivity and the dependence of silicate weathering on temperature are constrained. Next, the carbon cycle model is applied to all of Earth history to answer long-debated questions about the conditions on the early Earth. The Archean Earth was likely temperate (<40°C) with a slightly acidic to neutral ocean pH, contrary to the hot Archean climates or alkaline oceans that have previously been proposed. Taken as a whole, this thesis elucidates the processes that have maintained habitable surface conditions on Earth and uses this understanding to constrain surface conditions on the early Earth. Additionally, the development of a theory of disequilibrium biosignatures provides novel prospects for exoplanet life detection that could be realized with next generation telescopes.
Thesis (Ph.D.)--University of Washington, 2019
Keywords: astrobiology; biosignatures; carbon cycle; climate; exoplanets; weathering; Biogeochemistry; Astronomy; Geology; Earth and space sciences